2016
DOI: 10.1021/acsbiomaterials.6b00170
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing PDMS Elastomer in a Hydrophilic Support Bath via Freeform Reversible Embedding

Abstract: Polydimethylsiloxane (PDMS) elastomer is used in a wide range of biomaterial applications including microfluidics, cell culture substrates, flexible electronics, and medical devices. However, it has proved challenging to 3D print PDMS in complex structures due to its low elastic modulus and need for support during the printing process. Here we demonstrate the 3D printing of hydrophobic PDMS prepolymer resins within a hydrophilic Carbopol gel support via freeform reversible embedding (FRE). In the FRE printing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
338
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(342 citation statements)
references
References 16 publications
4
338
0
Order By: Relevance
“…For applications where a higher resolution is required, many techniques and products are available to adjust the rheological behavior of the PDMS precursor. [5,24,[43][44][45][46][47] The development of the hydrogel precursor for our extrusion printing was more demanding and required a balance between conductivity, stability, and rheological characteristics.…”
mentioning
confidence: 99%
“…For applications where a higher resolution is required, many techniques and products are available to adjust the rheological behavior of the PDMS precursor. [5,24,[43][44][45][46][47] The development of the hydrogel precursor for our extrusion printing was more demanding and required a balance between conductivity, stability, and rheological characteristics.…”
mentioning
confidence: 99%
“…Then, the whole liquid structure is solidified in situ by applying suitable cross-linking mechanisms [74,75]. Hinton et al [76] demonstrated a new method of 3D printing polydimethylsiloxane (PDMS) using a hydrophilic Carbopol support bath. Carbopol support acts as a Bingham plastic that yields and fluidizes when the syringe tip of the 3D printer moves through it, but acts as a solid for the PDMS extruded within it.…”
Section: Support Bathsmentioning
confidence: 99%
“…After the printing is completed, the fugitive inks are transformed from a gel to a liquid by simply altering the temperature and then the resulting liquid can be drained away leaving the bioprinted structure behind. Fugitive inks are used in two ways, either around the structure (in the form of a supporting bath) to support its creation in free space [1][2][3] or inside the structure to enable the creation of internal channels [4].…”
Section: Fugitive Inksmentioning
confidence: 99%
“…Previously when printing within a hydrogel, filler material is required to restore the resulting voids and crevasses left by the nozzle as it travels through the hydrogel material [1]. However, a new technique called Freeform Reversible Embedding of Suspended Hydrogels (FRESH) [2], or more simply Freeform Reversible Embedding (FRE) [3], has been developed which uses a supporting bath composed of a material that exhibits a Bingham plastic rheology, flowing as a viscous fluid at high shear stresses but behaving as a rigid body at lower shear stresses. Due to this property of the bath, the syringe nozzle can travel through the supporting material with negligible resistance while the extruded material is supported and the geometry of the printed structure is maintained.…”
Section: Fugitive Support Bathsmentioning
confidence: 99%
See 1 more Smart Citation